Sometimes neither water nor fire are more useful than friendship—a new risk score for prediction of contrast-induced nephropathy (CIN) and long-term adverse outcomes in patients undergoing coronary angiography - De Filippo, Ovidio; D’Ascenzo, Fabrizio; Piroli, Francesco; Budano, Carlo; De Ferrari, Gaetano Maria (Journal of Thoracic Disease, 2019)
Non aqua non igni locis pluribus utimur quam amicitia. Cicerone, Marco Tullio (106-43 a.C.) (De amicitia: VI, 32)